Pelatihan Manajemen Produksi dan Digital Marketing Untuk Inovasi Jamu Tradisional "Larasati" dalam Menghadapi Era Kompetisi Ekonomi Digital - Kurniawati Darmaningrum; Rahmatya Widyaswati; Istinganah Eni Maryanti (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to increase the understanding and skills of Jamu Larasati partners in managing production, digital marketing, financial management, and business financial reports. The method for implementing this service used training and FGD. The instrument for evaluating this activity used practice sheets and was analyzed descriptively. The results of this service showed that partners' understanding and skills in production management, digital marketing, and financial management have increased. It was proven by partners who had increased production quantity from 100 bottles per day to 120-150 bottles per day. Partners also had abilities related to digital marketing, proven by partners having the ability to use SEO and create marketing content that suits their business. Apart from that, partners also had financial management skills, as proven by partners having financial reports and being able to analyze the results of financial reports.